1B.11: ACCURACY OF DIFFERENT TYPES OF BLOOD PRESSURE MEASURING DEVICES AT HIGH ALTITUDE. DATA FROM HIGHCARE-ALPS STUDY. (June 2015) - Bilo, G.; Faini, A.; Liu, X.; Lisi, E.; Hoshide, S.; Salerno, S.; Giuliano, A.; Gregorini, F.; Revera, M.; Lang, M.; Caravita, S.; Soranna, D.; et al.
Abstract : Objective: Blood pressure (BP) measuring devices may become inaccurate at high altitude due to low barometric pressure. Aim of this study was to assess the changes in the accuracy of different types of BP measuring devices between sea level and high altitude, taking auscultatory measurements with mercury sphygmomanometer as reference. Design and method: In the frame of HIGHCARE-ALPS project, we obtained multiple BP measurements in 39 healthy, normotensive volunteers (age:36.4 ± 8.5y,  M/F:21/18), using a mercury (MER, reference), an aneroid (ANE), and two validated oscillometric devices [one for home (OSC-HBP; AND UA-767PC) and one for ambulatory (OSC-ABP; AND TM2430)] BP monitoring, at sea level and during acute exposure to high altitude (4559m, 437–439 Torr). BP measurements with the different devices were performed sequentially on the same arm in random order, consistent under both study conditions. Results: Mean systolic (S) and diastolic (D)BP were higher at high altitude than at sea level (MER: 117.6/80.3 vs. 110.9/74.1 mmHg, p < 0.001) The mean differences in SBP between MER (reference) and the other devices at baseline and high altitude were 1.7 ± 6.5/0.6 ± 7.1 (OSC-ABP), −3.1 ± 5.3*/−3.8 ± 6.3* (ANE) and −1.2 ± 7.0/−5.0 ± 6.7* (OSC-HBP) respectively. The corresponding differences for DBP were −3.9 ± 5.9*/−4.5 ± 6.5* (OSC-ABP), −2.2 ± 5.1*−5.3 ± 6.7* (ANE) and −4.8 ± 7.6*/−1.8 ± 7.1 (OSC-HBP), (mmHg, *p < 0.01 vs. MER). The over or underestimations of BP values by tested devices as compared with MER were consistent and similar at sea level and high altitude, except for a greater underestimation of SBP by OSC-HBP (p = 0.01), and of DBP by ANE (p = 0.03) at altitude, and for a greater underestimation of DBP by OSC-HBP (p = 0.02) at sea level. In spite of the statistical significance, the absolute changes in the size of error between sea level and high altitude never exceeded 4 mmHg. The distribution of mean between-device differences within the group was consistent between sea level and high altitude, with about 50% of subjects displaying between-devices differences always smaller than 5 mmHg (Figure). Figure. No caption available. Conclusions: BP measuring devices commonly used at sea level remain reasonably accurate at high altitude. We did not find consistent and clinically relevant changes in the accuracy of the tested devices caused by low barometric pressure at altitude.